Determinants of Disclaimers in the Auditor’s Opinion on the Financial Statement - Włodarczyk, Anna Maria; Białek-Jaworska, Anna Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article aims to identify the determinants of obtaining other than qualified audit opinion by public companies listed on the Warsaw Stock Exchange, based on an analysis of financial statements prepared in accordance with International Financial Reporting Standards (IFRS) and determining signs of their impact on the probability of receiving such an opinion. The empirical research on the role of an audit opinion in the protection of funds provider’s interests was conducted with the use of logit model on panel data containing 980 observations of 245 companies in the period of 2010–2013. The results indicate that following factors have significant impact on firms obtaining audit opinion which is other than qualified: liquidity, debt, corporate governance approximated by share of major shareholders in company’s equity, viability, firm size and risk of a company’s default. The stronger the corporate governance (higher share of major shareholders in the company’s equity) the lower the probability for the company of obtaining the audit opinion which is other than qualified. The results obtained in the research may be considered as original contribution to the literature. The research does not confirm any significant linkage between the quality of service provided by auditors (approximated by the reputation and the size of the audit company belonging to the Big 4) and the probability of obtaining the audit opinion which is other than qualified.